The Strategic Environment Assessment bibliographic network: A quantitative literature review analysis - Caschili, Simone; De Montis, Andrea; Ganciu, Amedeo; Ledda, Antonio; Barra, Mario (Environmental impact assessment review, 2014)
Academic literature has been continuously growing at such a pace that it can be difficult to follow the progression of scientific achievements; hence, the need to dispose of quantitative knowledge support systems to analyze the literature of a subject. In this article we utilize network analysis tools to build a literature review of scientific documents published in the multidisciplinary field of Strategic Environment Assessment (SEA). The proposed approach helps researchers to build unbiased and comprehensive literature reviews. We collect information on 7662 SEA publications and build the SEA Bibliographic Network (SEABN) employing the basic idea that two publications are interconnected if one cites the other. We apply network analysis at macroscopic (network architecture), mesoscopic (sub graph) and microscopic levels (node) in order to i) verify what network structure characterizes the SEA literature, ii) identify the authors, disciplines and journals that are contributing to the international discussion on SEA, and iii) scrutinize the most cited and important publications in the field. Results show that the SEA is a multidisciplinary subject; the SEABN belongs to the class of real small world networks with a dominance of publications in Environmental studies over a total of 12 scientific sectors. Christopher Wood, Olivia Bina, Matthew Cashmore, and Andrew Jordan are found to be the leading authors while Environmental Impact Assessment Review is by far the scientific journal with the highest number of publications in SEA studies. •We utilize network analysis to analyze scientific documents in the SEA field.•We build the SEA Bibliographic Network (SEABN) of 7662 publications.•We apply network analysis at macroscopic, mesoscopic and microscopic network levels.•We identify SEABN architecture, relevant publications, authors, subjects and journals.